2023
DOI: 10.1111/dom.15378
|View full text |Cite
|
Sign up to set email alerts
|

Association of five diet scores with severe NAFLD incidence: A prospective study from UK Biobank

Fanny Petermann‐Rocha,
Fernanda Carrasco‐Marin,
Jirapitcha Boonpor
et al.

Abstract: AimThis study aimed to contrast the associations of five common diet scores with severe non‐alcoholic fatty liver disease (NAFLD) incidence.Materials and MethodsIn total, 162 999 UK Biobank participants were included in this prospective population‐based study. Five international diet scores were included: the 14‐Item Mediterranean Diet Adherence Screener (MEDAS‐14), the Recommended Food Score (RFS), the Healthy Diet Indicator (HDI), the Mediterranean Diet Score and the Mediterranean‐DASH Intervention for Neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 57 publications
(146 reference statements)
0
1
0
Order By: Relevance
“…Hanachi M et al demonstrated that a BMI < 12 was the sole independent risk factor for hepatic cytolysis in a study conducted in patients with anorexia nervosa [ 21 ]; furthermore, other studies have shown that increased caloric consumption and weight gain can lead to a rapid improvement in liver function tests [ 22 ]. Liver abnormalities have been reported as complications of other clinical conditions associated with impairment of nutrient absorption, such as bariatric surgery and intestinal failure [ 23 , 24 ]. These results support evidence from previous observations: chronic liver disease, ranging from steatosis (fatty liver) to steatohepatitis, acute alcohol-associated hepatitis, and liver cirrhosis, is associated with malnutrition, especially among hospitalized patients due to an inadequate intake of both macro- and micro-nutrients, leading to higher mortality and complications [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hanachi M et al demonstrated that a BMI < 12 was the sole independent risk factor for hepatic cytolysis in a study conducted in patients with anorexia nervosa [ 21 ]; furthermore, other studies have shown that increased caloric consumption and weight gain can lead to a rapid improvement in liver function tests [ 22 ]. Liver abnormalities have been reported as complications of other clinical conditions associated with impairment of nutrient absorption, such as bariatric surgery and intestinal failure [ 23 , 24 ]. These results support evidence from previous observations: chronic liver disease, ranging from steatosis (fatty liver) to steatohepatitis, acute alcohol-associated hepatitis, and liver cirrhosis, is associated with malnutrition, especially among hospitalized patients due to an inadequate intake of both macro- and micro-nutrients, leading to higher mortality and complications [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%